Pengaruh Dukungan Organisasi terhadap Kinerja Karyawan Melalui Keterikatan Karyawan sebagai Mediator (Studi pada Balai Perikanan Budidaya Air Tawar Sungai Gelam) - Fitriani Fitriani; Shofia Amin; Besse Wediawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to analyze the effect of Organizational Support on Employee Performance through Employee Engagement (study at the Gelam Jamb River Freshwater Aquaculture Center)i. The target population for this research is BPBAT ASN totaling 67 employees with 50 respondents as BPBAT Sungai Gelam ASN technical personnel. This study uses a quantitative approach with survey methods and uses Partial Least Square (PLS) data analysis. The results of this study indicate thato Organizational support has a negative and insignificant effect on performance,Organizational support has a positive and significant effect on employee engagement, employee engagement has a positive and significant effect on performance, Organizational support has a positive and significant effect on performance through employee engagement. Employee engagement is proven as a mediating variable in Organizational Support on the performance of the employees of the Sungai Gelam Sungai Gelam Fisheries Freshwater Center, Jambi.Â